Restless bones - French, Gillian (Shaw Connolly mystery, 2026)
"When a missing woman's body is discovered in a submerged car one year after her disappearance, Shaw Connolly is called to process the scene. She finds a single print belonging to a long-dead female ex-con; could it be the key to identifying the murderer? As usual, Shaw won't stop looking until she's dredged up more than a few hidden crimes. All the while, Shaw's past won't let her go. Just as the Connolly family begins to find some peace after the arrest of Shaw's sister's killer, Anders Jansen, Shaw receives a request from her state police contact. Anders, in prison awaiting trial, has claimed responsibility for the murders of two other young women whose cases have grown cold over the past decade. But he refuses to help the police unless Shaw agrees to act as a special consultant in the search. Despite her misgivings--Anders's love of malicious mind games is as toxic as ever--Shaw could never prolong another family's suffering. Her agreement to assist jeopardizes not only the fragile healing of her own family's wounds, but the rebuilding of her marriage and her relationship with her youngest son, who's colliding with some hard truths of how cruel people can be. It seems, for Shaw, closure is a long way off . . . but danger may be closer than she thinks"-- Provided by publisher.